PENGANIAYAAN TERHADAP NARAPIDANA PELAKU PERKOSAAN YANG MENGALAMI LABEL NEGATIF DI LEMBAGA PEMASYARAKATAN (STUDI DI LEMBAGA PEMASYARAKATAN WIROGUNAN YOGYAKARTA) - Martha, Aroma Elmina; Khoirunnas, Chandra (Veritas et Justitia, 2018)
This article is a case study on the legal issues surrounding beatings and torture suffered by rape offenders incarcerated in the Wirogunan Prison, Yogyyakarta.  Purpose of this research is to identify profile of perpetrator and determinate what factors are behind this deviant behaviour.  This research uses a criminological method or approach. Data has been obtained from direct observation, expert interviews and literature review.  One of the important findings is that beatings and torture of rape offenders are justified by the general inmates on the basis of negative labelling given toward the offender and his crime.